A short history of the Phoenicians - Woolmer, Mark. (London ; New York)
xviii, 244 sayfa, [4] sayfa harita
Keywords: “Offering new insights based on recent archaeological discoveries in their heartland of modern-day Lebanon, Mark Woolmer presents a fresh appraisal of this fascinating, yet elusive, Semitic people. Discussing material culture, language and alphabet, religion (including sacred prostitution of women and boys to the goddess Astarte), funerary custom and trade and expansion into the Punic west, he explores Phoenicia in all its paradoxical complexity. Viewed in antiquity as sage scribes and intrepid mariners who pushed back the boundaries of the known world, and as skilled engineers who built monumental harbour cities like Tyre and Sidon, the Phoenicians were also considered (especially by their rivals, the Romans) to be profiteers cruelly trading in human lives. The author shows them above all to have been masters of the sea: this was a civilization that circumnavigated Africa two thousand years before Vasco da Gama did it in 1498. The Phoenicians present a tantalizing face to the ancient historian. Latin sources suggest they once had an extensive literature of history, law, philosophy and religion; but all now is lost. In this revised and updated edition, Woolmer takes stock of recent historiographical developments in the field, bringing the present edition up to speed with contemporary understanding.“ --